Pseudotumor cerebri in carcinoma cervix: “A diagnostic dilemma” (Indian Journal of Case Reports, 2021)
Pseudotumor cerebri, commonly known as idiopathic intracranial hypertension or benign intracranial hypertension, is a rare syndrome that presents mainly as a result of raised intracranial pressure (ICP). The diagnosis of this condition is established by the exclusion, with the aid of radiological imaging, and examination of cerebrospinal fluid. Due to the aggressive nature of this disease, both signs and symptoms may be intermittent, making definitive diagnosis difficult. Here, we present the case of a 60-year-old female with Stage III carcinoma cervix that was treated with concurrent chemoradiation with weekly cisplatin. She completed the concurrent chemoradiation and developed intermittent seizures, headache, weakness of lower limbs, and visual disturbances. A diagnosis of pseudotumor cerebri was entertained using the modified Dandy Criteria. Pseudotumor cerebri should be considered in cancer patients presenting with raised ICP of sudden onset in the absence of clinical and radiological evidence of brain metastases.